Proteomic analysis of s-acylated proteins in human retinal pigment epithelial cells and the role of palmitoylation of Niemann-Pick type C1 protein in cholesterol transport - Li, Jia Kai; Rao, Yu Qing; Koh, Siew Kwan; Zhao, Peiquan; Zhou, Lei; Li, Jing (Frontiers in Aging Neuroscience, 2022)
Palmitoylation is a dynamic process that regulates the activity of the modified proteins. Retinal pigment epithelial (RPE) cells play pivotal roles in the visual cycle and maintaining healthy photoreceptor cells. Dysfunctional RPE cells are often associated with degenerative retinal diseases. The aim of the study was to identify potentially palmitoylated proteins in human RPE cells. By using the detergent-resistant membrane, we found 312 potentially palmitoylated peptides which corresponded to 192 proteins in RPE cells, including 55 new candidate proteins which were not reported before. Gene enrichment analysis highlighted significant enrichment of palmitoylated proteins in cell-matrix adhesion, cell-cell recognition, protein cellular localization, and translation, among others. We further studied the effect of 3 potential palmitoylation sites (Cys 799, 900, and 816) of Niemann–Pick type C1 protein (NPC1) on cholesterol accumulation. We found that mutation of any single Cys alone had no significant effect on intracellular cholesterol accumulation while simultaneous mutation of Cys799 and 800 caused significant cholesterol accumulation in the late endosome. No further cholesterol accumulation was observed by adding another mutation at Cys 816. However, the mutation did not alter the cellular localization of the protein. Conclusions: PRE cells have an abundant number of palmitoylated proteins which are involved in cellular processes critical to visual function. The palmitoylation at Cys799 and 800 was needed for cholesterol export, but not the intracellular localization of NPC1.